Early Growth Behaviour of Wheat Genotypes as Affected by Polyethylene Glycol (PEG-6000): Polyethylene Glycol-6000 for Wheat Genotype (Biological Sciences - PJSIR, 2016)
Polyethylene glycol (PEG-6000) is often used for the early establishment screening of the wheatgenotypes against drought stress conditions. A collection of twenty-one newly developed bread wheatgenotypes (developed through conventional and mutational breeding techniques) and four commercial droughttolerant check varieties were included in screening at seedling stage under three treatments of PEG-6000;T1 (0.5 MPa) and T2 (0.75 MPa) along with control T3 (distill water only). Three important early growthestablishment traits like germination percentage, root length and shoot length of the wheat genotypes wereobserved. Significant variation among genotypic means regarding the observed traits was recorded at boththe treatments. Wheat genotypes performance including check varieties for germination percentages wasrecorded as T1 (86.1%), T2 (72.4%) with reduction percentage of 12.5% and 33.8%. Root length of genotypesdecreased by 37.0% in 0.5 MPa and 82.75% in 0.75 MPa, whereas, shoot length reduction was recorded as38.9% (T1) and 84.6% (T2) as compared to control. This study provided essential information about theperformance of advanced wheat genotypes under water stress conditions at early seedling establishment.